2012
DOI: 10.1248/bpb.35.967
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Event Profile of Tigecycline: Data Mining of the Public Version of the U.S. Food and Drug Administration Adverse Event Reporting System

Abstract: The recent emergence of multidrug-resistant pathogens and/or pharmacokinetics-pharmacodynamics considerations may result in off-label use of a certain class of antibacterials, including tigecycline. This study was performed to clarify the safety profile of tigecycline in the user-derived manner and to compare it with the prescribing information provided by the manufacturer. Numerous spontaneous adverse event reports (AERs) submitted to the U.S. Food and Drug Administration (FDA) were analyzed after a revision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 19 publications
0
47
1
Order By: Relevance
“…Additionally, this system was used to evaluate susceptibility to hypersensitivity reactions for 14 anticancer agents, and it was found that the number of co-occurrences was an important factor in signal detection 22, 23. Very recently, this system was applied to the evaluation of adverse drug events induced by statins 24, capecitabine 25 and tigecycline 26, and again the reproducibility of clinical observations was suggested, providing that the number of co-occurrences was large enough to detect a signal.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this system was used to evaluate susceptibility to hypersensitivity reactions for 14 anticancer agents, and it was found that the number of co-occurrences was an important factor in signal detection 22, 23. Very recently, this system was applied to the evaluation of adverse drug events induced by statins 24, capecitabine 25 and tigecycline 26, and again the reproducibility of clinical observations was suggested, providing that the number of co-occurrences was large enough to detect a signal.…”
Section: Discussionmentioning
confidence: 99%
“…and Stenotrophomonas maltophilia) (3), and anaerobic bacteria (4) having relatively high sensitivities. Kadoyama et al (5) summarized a total of 248 tigecycline-related adverse reactions, the most common being nausea, vomiting, elevated levels of alanine aminotransferase, bilirubin, alkaline phosphatase, and aspartate aminotransferase, and hepatic dysfunction. In a number of studies, patients showed good tolerance of tigecycline, indicating that it is safe (6-7).…”
mentioning
confidence: 99%
“…Pancreatitis has been identified in pharmacovigilance databases during post-approval use of tigecycline. 9,11,12 Because these reactions are reported voluntarily from a population of uncertain size, it is not always possible to reliably estimate their frequency or establish causal relationship to drug exposure.…”
Section: Discussionmentioning
confidence: 99%